The what, where, who, why, which, and how of collaborative play involving autistic children in educational context: a contextual inquiry - Hijab, Mohamad Hassan Fadi; Khattab, Shaza; Al Aswadi, Nahwan; Neves, Joselia; Qaraqe, Marwa; Othman, Achraf; Alsulaiti, Noora; Al-Thani, Dena (Frontiers in Education, 2024)
Introduction: In educational settings, autistic children often encounter barriers to engaging in collaborative play. Notably, play is an important component of a child's development, and its pedagogical significance has been rigorously researched. This study endeavored to understand the dynamics of collaborative play among autistic children across various learning contexts, examining usual methodologies, associated challenges, and potential technological constraints influencing the collaborative play among autistic children.Methods: The study was conducted in two diverse environments, an inclusive international school and a special education center, both located in Qatar, and both with a significant population of autistic children. The data was gathered through a series of 45 interviews with a diverse group of proxies, including therapists, teachers, and parents. Furthermore, 48 observation sessions were conducted with the autistic children in both settings. The data from the interviews and observation sessions were analyzed using inductive reasoning to perform a thematic analysis.Results: The study elicited six key themes from the interviews, coined as '5W-H', which encompassed the aspects of who (Actor), where (Location), what (Tool), why (Purpose), which (Sense), and how (Process) in terms of how collaborative play was conducted. From the observation sessions, another four themes were derived, which centered on collaborative play, potential for collaboration, coordinated activity, and collaborative activity.Discussion: The findings of this study provide valuable insights into the practice of collaborative play among autistic children, serving as a useful resource to guide future research agenda and educational 2 This is a provisional file, not the final typeset article practices. Understanding these dynamics can aid in developing more effective educational strategies and technologies to enhance the collaborative learning experiences of autistic children.